TELEIMMERSIVE ARCHAEOLOGY (Archeomatica, 2012)
Teleimmersive archaeology is still in embryonic stage of development but this system is the ï¬ rst one of this kind created worldwide and opens very challenging perspectives in archaeology. The project was supported by the University of California, Merced (School of Social Sciences, Humanities and Arts), and the University of California, Berkeley, CITRIS (Center for Information Technology and Society), where we have started the development of a collaborative system for archaeology, based on Teleimmersive Technology. Archeologia teleimmersivaIl progetto di Archeologia teleimmersiva è supportato dal Center for Information Technology Research in the Interest of Society (CITRIS) dell'Università  di Berkeley. È ancora in uno stato embrionale ma è il primo sistema creato su scala mondiale che apre prospettive di cam-biamento all'archeologia. La Ciberarcheologia rappresenta un nuovo campo della ricerca volto alla simulazione e investigazione delle in-terpretazioni del passato.